Ekowisata Melalui Konsep Community Based Tourism - Rini Anggriani; Widia Febriana; Rahman Prasetyo; Rina Komala (JCOMENT (Journal of Community Empowerment), 2023)
Tourism is the most dynamic sector in many countries. Especially in developing countries, tourism is one of the biggest contributors to foreign exchange. Almost all studies regarding the impact of the tourism sector on the economy. shows that the development of tourism in an area is able to make a sizable contribution to the regional economy such as the level of people's income, increasing foreign exchange earnings, absorbing labor, alleviating unemployment, encouraging business opportunities, encouraging equitable development, poverty alleviation because the opening of employment opportunities ultimately boils down to to increasing the welfare of society as a whole. The East Lombok Sembalun area is one of the provinces that has the highest number of tourist visits since the last 5 years. In this study the authors used a quantitative descriptive research method. So called because the data in this study are quantitative. Based on the results of the research involving a sample of 50 respondents above, the achievement of Sembalun Tourism Village is at an interval of 94.5%, namely in the SB (Very Successful) category providing socio-economic benefits to the people of Sembalun Tourism Village, West Nusa Tengga.